Fleabag. Season 1 [videorecording (DVD)] - Waller-Bridge, Phoebe, 1985- (Screen Media Films, 2020)
A dry-witted, sexual, angry, grief-riddled woman hurls herself at modern living in London. She often escapes into momentary fantasy asides -- letting an imaginary audience hear her unspoken gibes -- as she navigates her father's emotional distance, her godmother-turned-stepmother, her perfect sister and horrible brother-in-law as well as her seemingly-doomed love life.